Geographies of transition in food systems: the role of Metropolitan Areas in the Portuguese case - Ferreiro, Maria de Fátima; Salavisa, I.; Bizarro, S. (The 8th Nordic Geographers Meeting, 2019)
The transition of food systems towards a sustainable model has been under analysis and debate (Sutherland, Wilson and Zagata 2014). This transition is related with structural changes, namely the emphasis on local production, short supply chains, and the preference for bio products. So far the research has mostly highlighted the role of agriculture through niche innovations (e.g. Wuskerke and van der Ploeg, 2004; Knickel et al., 2009) and organic farms (Belz, 2004; Smith, 2007), transitions within individual farms (Wilson, 2008), and national cases (Poppe et al., 2009). In the case of food systems transition, the centrality of territorial units and scales has been claimed as fundamental (Spaargaren et al, 2012). This consideration will contribute to emphasize the relevance of territorial dimensions in the transitions literature. Bearing this in mind, the paper addresses the role of Metropolitan Areas in the food systems transition through the consideration of the case of Lisbon Metropolitan Area (LMA). Recent research projects (e.g., Periurban) have studied the LMA, allowing the identification of crucial resources for the transition process, such as a strong presence of agricultural land (around 45% of LMA land area). The strategic role of this specific territory is addressed through the following analytical dimensions: i) characterization of Lisbon Metropolitan Area in socioeconomic and governance terms, namely land use patterns, and territory planning and management institutional framework; ii) presentation of innovative case studies located in LMA within the theoretical framework of transition studies.